LITERATURE REVIEW : CHARACTERISTIC ANALYSIS PHYSICAL CHEMISTRY PROPERTIES (ACIDITY, FLOW RATE, CONSISTENCY) SALIVA RADIOTHERAPY HEAD & NECK CANCER PATIENT - Muhammad Henri Indrawan; Rizki Amalina; Febia Astiawati Sugiarto (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
Background: Head and Neck Cancer (oral, nose, pharynx, and larynx area) are 890.000 new cases and 450.000 deaths in 2018. One of the treatment’s Radiotherapy affects saliva’s quality in physicochemical properties (flow rate, consistency, and acidity). Physicochemical properties are analyzed because they can influence saliva’s quality. The study is to get updated analysis about physicochemical properties’ saliva in Radiotherapy of Head and Neck Cancer Patient. Method: There are 39.972 articles, searched in Google Scholar, Academia, and Microsoft Academy database. The articles that are connected with keywords topic are 52 articles with abstract and title screening processes. The next process is selecting articles and getting 17 excluding articles and 35 including articles. The total articles are 35 articles. Therefore, they’re ready to be analyzed.Result: Major result of the analysis is radiotherapy affecting patients with Xerostomia. There’s a reducing flow rate, increasing consistency, and pH decrease in the acute phase. In the late phase, physicochemical properties’ saliva quality is decreased because of high ionizing radiation damaging DNA and membrane of the acinar cell. Primary saliva became hypertonic because protein kinase A enzyme and protein kinase C enzyme fail to do phosphorylation to build protein materials in the acinar cell. Conclusion: Radiotherapy making Xerostomia impact decreasing physicochemical properties’ quality in head and neck cancer. Education is the main thing to take Xerostomia’s complications for maintaining OHI like teeth brushing, chlorhexidine, fluoride or salivary stimulant application, and others. Analysis can be developed for the observation of consistency outcomes based on quantity.